The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/bjso.12167
|View full text |Cite
|
Sign up to set email alerts
|

Group differences in the legitimization of inequality: Questioning the role of social dominance orientation

Abstract: Social dominance orientation (SDO) is conceived as an individual's level of support for group-based hierarchy in general that causes support for more specific group hierarchies. According to social dominance theory, group differences in SDO underpin ideological and behavioural group differences related to specific group hierarchies. Using representative 5-year longitudinal panel data from New Zealand (N = 3,384), we test whether SDO mediates effects of sex and ethnicity on legitimizing myths (LMs) relating to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…The most consistent finding is that social dominance orientation is positively associated with HS in both men and women (e.g., Christopher & Mull, 2006; Ruthig et al, 2017; Sibley & Overall, 2011), although some articles find this association only for men (e.g., Schmitt & Wirth, 2009; Stewart, 2017). In longitudinal designs, social dominance orientation predicts increases in HS (but not BS) over time (Pehrson et al, 2017; Sibley, Wilson, & Duckitt, 2007 [among men]). A path model linking this association to personality and social worldviews among men further indicated that the social dominance orientation link to HS stems from perceptions of the world as a competitive place (a “dog-eat-dog” world) and a personality disposition high in tough-mindedness (Sibley, Wilson, & Duckitt, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most consistent finding is that social dominance orientation is positively associated with HS in both men and women (e.g., Christopher & Mull, 2006; Ruthig et al, 2017; Sibley & Overall, 2011), although some articles find this association only for men (e.g., Schmitt & Wirth, 2009; Stewart, 2017). In longitudinal designs, social dominance orientation predicts increases in HS (but not BS) over time (Pehrson et al, 2017; Sibley, Wilson, & Duckitt, 2007 [among men]). A path model linking this association to personality and social worldviews among men further indicated that the social dominance orientation link to HS stems from perceptions of the world as a competitive place (a “dog-eat-dog” world) and a personality disposition high in tough-mindedness (Sibley, Wilson, & Duckitt, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Most articles focused either on both social dominance orientation and right-wing authoritarianism (e.g., Feather & McKee, 2012) or solely on social dominance orientation (e.g., Radke, Hornsey, Sibley, & Barlow, 2018), with fewer articles dealing solely with right-wing authoritarianism (e.g., Patev et al, 2019). The reported correlations between the ambivalent sexism constructs and these social ideologies are either direct (e.g., Mosso et al, 2013) or reported as part of broader mediational models (e.g., Pehrson et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…El sexismo benevolente, en apariencia bien intencionado (Dardenne et al, 2007;Stedham & Wieland, 2017), es condescendiente y se fundamenta en la premisa de que los hombres deben ser arriesgados y evitar la debilidad, mientras las mujeres requieren de su protección (Glick & Fiske, 1996;, son cuidadoras y evitan ser dominantes (Koenig, 2018). Este tipo de sexismo debilita a la mujer (Dardenne et al, 2007;Pesce & Etchezahar, 2020), afectando su percepción de competencia o autoeficacia (Dumont et al, 2010;Pehrson et al, 2017). De manera complementaria, el sexismo benevolente se ha asociado empíricamente con el tradicionalismo y la dominancia (Austin & Jackson, 2019) con la tolerancia con el uso de tácticas agresivas de persuasión sexual masculina (Garrido Macías et al, 2017) y con la adopción de prácticas de salud no seguras (Orozco-Idárraga et al, 2021) en el contexto de las relaciones heterosexuales íntimas (Becker & Wright, 2011;Glick & Raberg, 2018;Hideg & Ferris, 2016;Jost & Kay, 2005).…”
Section: Sexismo Y Génerounclassified